2011
DOI: 10.1016/j.anorl.2010.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Clear-cell renal carcinoma metastasis to the base of the tongue and sphenoid sinus: Two very rare atypical ENT locations

Abstract: Such metastases may sometimes occur years after the discovery of the primitive renal tumor; any history of kidney cancer should, therefore, be noted in patients with suspect ENT lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 8 publications
1
15
0
1
Order By: Relevance
“…17 In the second part of our analysis, we focused our attention on the organ-specific effect of metastases. Although RCC can metastasise to virtually any organ, 18 we confirmed that lung and bone represent the two at a higher prevalence of metastases from RCC, at least in patients who are candidates for surgical debulking. Interestingly, conversely to bone or liver, multiple metastases frequently affect lungs without any other site affected.…”
Section: Discussionsupporting
confidence: 69%
“…17 In the second part of our analysis, we focused our attention on the organ-specific effect of metastases. Although RCC can metastasise to virtually any organ, 18 we confirmed that lung and bone represent the two at a higher prevalence of metastases from RCC, at least in patients who are candidates for surgical debulking. Interestingly, conversely to bone or liver, multiple metastases frequently affect lungs without any other site affected.…”
Section: Discussionsupporting
confidence: 69%
“…Due to low radiosensitivity, surgery is the preferred option if the tumor can be resected without unacceptable functional sequelae [15] .…”
Section: Discussionmentioning
confidence: 99%
“…First-line treatment is surgical, due to low radiosensitivity, with radiation therapy as a possible second line [10][11].…”
Section: Discussionmentioning
confidence: 99%